Identifying drivers of the Malaysian economy using policy-relevant measures - Saari, Mohd Yusof; Utit, Chakrin; Hamid, Nur Adilah; Maji, Ibrahim Kabiru; Hassan, Azman (Faculty of Economics & Administration, University of Malaya and Malaysian Economic Association, 2017)
Input-output linkages and multipliers are the two measures that are frequently used to find the drivers of an economy. Deriving from these two measures based on the traditional approach fails to consider the relative sectoral sizes. This paper introduces new linkage and multiplier measures that do not solely adjust for the relative sizes, but also extend the measures for policy-relevant indicators in Malaysia. Comparing the results between the traditional approach and the new approach, there is a clear indication that the former incorrectly identified the drivers of the Malaysian economy. The traditional approach not only introduced bias in linkages, but also overestimated the actual size of the multipliers. The new linkage and multiplier measures that were developed in this paper can be applied for other economies in finding key drivers for specific policy goals.